Literature Review: Individual Personality Effect on Human Resource Planning Mediated by Organizational Commitment - Dwidyah Laurensyah Heriyanto Putri; Endang Dwiyanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Organizational commitment is one of the main factors that influence how human resource planning will be taken. This is inseparable from the influence of organizational commitment in many areas of human resource management. On the other hand, personality that influences organizational commitment is an essential part that is inherent in every individual that makes it difficult to change. Therefore, this study aims to determine the effect of individual personality on organizational commitment which indirectly affects organizational human resource planning. From the results obtained, personality in general has a significant influence on organizational commitment. However, a more in-depth study is needed using each personality theory and specific organizational fields.